2023
DOI: 10.1007/s13760-023-02204-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk and characteristics of Bell’s palsy in adults as an adverse event following COVID-19 vaccination: a retrospective study

Abstract: Background Although an association between COVID-19 vaccination and Bell’s palsy (BP) has been reported, a clear causal relationship has not been elucidated. We investigated the risk and clinical characteristics of BP after COVID-19 vaccination. Methods This retrospective chart review evaluated the association between COVID-19 vaccination and BP by comparing the number of patients diagnosed with BP during the pre-COVID-19 vaccination period (March 2018–February 2021) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a retrospective study of 13 patients who developed facial palsy within 42 days after vaccination, Kim et al reported that COVID-19 vaccines, especially mRNA vaccines, may be correlated with facial palsy with distinct clinical characteristics, which occurs more frequently in young adults and is often accompanied by changes in taste. It showed faster and better recovery compared with vaccine-unrelated facial palsy [12]. In contrast, Shemer et al reported no increase in the risk of facial paralysis after vaccination in a case-control study involving 37 patients with acute-onset facial paralysis and matched controls [13].…”
Section: Discussionmentioning
confidence: 92%
“…In a retrospective study of 13 patients who developed facial palsy within 42 days after vaccination, Kim et al reported that COVID-19 vaccines, especially mRNA vaccines, may be correlated with facial palsy with distinct clinical characteristics, which occurs more frequently in young adults and is often accompanied by changes in taste. It showed faster and better recovery compared with vaccine-unrelated facial palsy [12]. In contrast, Shemer et al reported no increase in the risk of facial paralysis after vaccination in a case-control study involving 37 patients with acute-onset facial paralysis and matched controls [13].…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective study by Kim et al found that Bell’s palsy occurred more during the COVID-19 vaccination period than in the three pre-vaccination years. In Bell’s palsy that had a timely relation with COVID-19 vaccination (<42 days, n = 13, 12/13 vaccinated with mRNA vaccines), compared to the vaccine-unrelated facial neuropathy, prognosis was better, and the patients were younger [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms related to pituitary gland involvement may include headaches and vision changes, while damage to the cerebellum and cortex can cause neurological symptoms such as ataxia, dizziness, and impaired consciousness 216,265 . Numerous cases of acute, temporary, unilateral peripheral facial paralysis, or Bell's palsy, have been reported as AE 49,259,266 .…”
Section: Neurological Symptomsmentioning
confidence: 99%